2009
DOI: 10.1515/epoly.2009.9.1.1628
|View full text |Cite
|
Sign up to set email alerts
|

Starch–metal complexes and their rheology

Abstract: Changes in conductivity of 5 w/w% starch gels was studied on their titration with 0.1 M aqueous solutions of selected metal salts. Starch gels usually trapped around 10 mg metal ions per 1 g starch [Co(II), Cu(II), Fe(III), Ni(II)] and that value was only slightly dependent on starch origin (amaranthus, corn, potato, tapioca, waxy corn). Among salts studied (acetates, chlorides, nitrates) FeCl 3 and NiCl 2 were likely to be used because they hydrolyzed increasing conductivity of the solutions and formed micell… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 7 publications
(13 citation statements)
references
References 43 publications
0
12
1
Order By: Relevance
“…Our results demonstrated that the granular structure, resulting from starch biological origin, and the starch water content are important factors impacting accumulation of metal ions in the granules. These findings are contrary to the opinion of Ciesielski and Krystyjan (2009), who reported that the amount of cations entrapped by starch does not depend on either the starch origin or the salt anions.…”
Section: Influence Of Starch Botanical Origin and Hydrationcontrasting
confidence: 99%
See 3 more Smart Citations
“…Our results demonstrated that the granular structure, resulting from starch biological origin, and the starch water content are important factors impacting accumulation of metal ions in the granules. These findings are contrary to the opinion of Ciesielski and Krystyjan (2009), who reported that the amount of cations entrapped by starch does not depend on either the starch origin or the salt anions.…”
Section: Influence Of Starch Botanical Origin and Hydrationcontrasting
confidence: 99%
“…Other authors postulated that the entire salt molecules penetrate the granules where alkaline metal cations form the metal alcoholates (Oosten, 1990) while cations of high non-transition and transition groups coordinate to the polysaccharide hydroxyl groups creating the starch-metal complexes (Ahmad & Williams, 1999, Ciesielski & Tomasik, 2004a. Formation of such complexes has been confirmed for gels of different starches as well as for amylose and amylopectin (Ciesielski et al 2003;Ciesielski & Tomasik, 2004a, 2004bCiesielski & Krystyjan, 2009). The structure and stability of the complexes of some transition metals has been already estimated by quatum-mechanical simulations (Ciesielski, 2009).…”
Section: Introductionmentioning
confidence: 95%
See 2 more Smart Citations
“…All examined samples behaved as non‐Newtonian, pseudoplastic liquids (Fig. ) just as other starch systems . Based on the n values obtained from the Ostwald‐de Waele model fitted to the upper flow curves, it was noted that, with the increasing starch concentration in the film‐forming solution, the pseudoplasticity decreased and amounted to 0.64 and 0.71 for H0 and S0, respectively (Table ).…”
Section: Resultsmentioning
confidence: 81%